2019
DOI: 10.1590/1678-4162-11016
|View full text |Cite
|
Sign up to set email alerts
|

Aspectos da biologia reprodutiva de Boa constrictor constrictor: um estudo histológico dos testículos nos períodos reprodutivos de quiescência e máxima atividade

Abstract: RESUMO As serpentes pertencem ao segundo maior grupo dentro dos répteis, podendo apresentar sazonalidade quanto à espermatogênese, com produção descontínua ou contínua. O presente trabalho tem como objetivo caracterizar aspectos da biologia reprodutiva de Boa constrictor constrictor com base nos achados histológicos dos testículos nos períodos de máxima atividade (período de gametogênese) e quiescência. Os testículos de dois espécimes de Boa c. constrictor (7767 e 11752) foram cortados a uma espessura de 3μm e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 6 publications
2
7
0
Order By: Relevance
“…The testicular volume variation observed in the present study is similar to the ultrasound evaluation data in E. cechria (Garcia et al, 2015). The testicular volume variation is also reported in other snake species, as Boa c. constrictor (Garcia et al, 2015;Bento et. al., 2019), Boa c. occidentalis (Bertona and Chiaraviglio, 2003;Ibargüengoytía et al, 2006), Eunectes murinus (Garcia et al, 2015) and Gloydius halys caucasicus (Salehi et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The testicular volume variation observed in the present study is similar to the ultrasound evaluation data in E. cechria (Garcia et al, 2015). The testicular volume variation is also reported in other snake species, as Boa c. constrictor (Garcia et al, 2015;Bento et. al., 2019), Boa c. occidentalis (Bertona and Chiaraviglio, 2003;Ibargüengoytía et al, 2006), Eunectes murinus (Garcia et al, 2015) and Gloydius halys caucasicus (Salehi et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…In the present study we observed that E. cechria presented recrudescent (initiating gametogenesis) and reproductive stage (mature spermatozoa in the lumen of the seminiferous tubules) at different times of year with greater rainfall. On basis on rainfall and temperature graphs, and spermatogenic cycle chronology, we observed that the reproductive period (mature spermatozoa) in E. cenchria occurs in the higher rainfall and temperature rates period, as observed in other Boidae (Bertona and Chiaraviglio, 2003;Ibargüengoytía et al, 2006;Bento et al, 2019).…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Their data corroborate those of Pizzatto and Marques (2007) regarding the variation in testicles size. There is a relationship between testicular volume and breeding season (Bento et al, 2019; Fox, 1976; Shine, 1994; Volsoe, 1944; Zenuto et al, 2003).…”
Section: Discussionmentioning
confidence: 99%